Could marine aerosol contribute to deteriorate building materials from interior areas of lighthouses? An answer from the analytical chemistry point of view. (11th October 2013) - Morillas, Héctor; Maguregui, Maite; Gómez‐Laserna, Olivia; Trebolazabala, Josu; Madariaga, Juan Manuel
<x xml:space="preserve">Abstract</x> In this work, a multianalytical methodology based on a combination of spectroscopic techniques such as Raman spectroscopy and micro energy dispersive X‐ray fluorescence spectroscopy, and soluble salt analysis by means of ion chromatography followed by a correlation analysis of these data was applied, in order to identify the nature of the deterioration compounds present in different building materials located on inner rooms from the ground floor of the Igueldo lighthouse (San Sebastian, Basque Country, North of Spain), and in order to prove if marine aerosol could contribute to cause deterioration processes in this kind of materials. The main deterioration compounds identified were sulfate and nitrate salts. Taking into consideration the positioning of some materials, a gypsum plaster covering them could be the sulfate source responsible of the crystallisation process of a wide variety of sulfate salts. Nevertheless, in some areas were no gypsum plaster remains are present, ammonium sulfate crystallisations were identified. The presence of this kind of sulfate could suggest a possible sulfate input coming from the migration of ammonium sulfate (among other sulfate salts) carried on marine aerosol, which can be deposited on the facade of the lighthouse and migrate to its inner areas. The possible source of nitrates that could cause the crystallisation of a wide variety of nitrate salts identified in this work could be the infiltration of ammonium nitrates coming from seagull droppings from outdoor to indoor areas. Copyright © 2013 John Wiley & Sons, Ltd.